Implementation of One Indonesian Data by the Central Statistics Agency of East Nusa Tenggara Province - Jefirstson Richset Riwukore; Luis Marnisah; Fellyanus Habaora Fellyanus Habaora; Tien Yustini (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: The purpose of this study was to analyze the implementation of One Data Indonesia conducted by the Central Statistics Agency of East Nusa Tenggara Province. Research Methodology: This research was conducted for one month, starting from February 19, 2022, to March 13, 2022. This research is classified as qualitative research with a purposive sampling approach. Focus Group Discussion (FGD) was used to obtain data. Data sources consist of secondary and primary data. Data analysis was done descriptively. Results: The results showed that the implementation of one Indonesian data in the Province of East Nusa Tenggara through the role of the Central Statistics Agency for the Province of East Nusa Tenggara was still constrained from the aspect of infrastructure, coordination, and human resources both internally and externally. The problem of electrification and wireless networks is a technical problem that greatly affects aspects of the implementation of one Indonesian data. The problem of coordination which is still a sectoral ego further increases the obstacles to implementing one Indonesian data. Although BPS human resources have met the standards, internal aspects such as limited human resources and external constraints such as a lack of understanding of statistical literacy in the public further complicate the obstacles to implementing SDI in NTT. The government's attention to resolving existing obstacles is very urgent to accelerate the implementation and development of SDI in East Nusa Tenggara Province. Limitations: This research is still limited from the aspect of implementing the one data Indonesia program, from the aspect of the Central Statistics Agency as the implementer, and the Department of Communication and Information as of the guardian of the data. This research is still from the perspective of institutional perception. Contribution: This research can contribution in communication, management, and policy implemented.